2017
DOI: 10.1093/qjmed/hcx106
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in pregnancy: worse medical outcomes in type 1 diabetes but worse psychological outcomes in gestational diabetes

Abstract: This work highlights a potential role for targeted psychological interventions to address and relieve symptoms of anxiety and depression among pregnant women with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 23 publications
3
31
5
Order By: Relevance
“…A total sample of 71,036 pregnant women were included in the analyses. Among the 10 studies, six studies were conducted in USA [15,18,20,22], two studies were conducted in Australia [16,26], and one study conducted each in Brazil [11], Canada [24], Greece [27] and Ireland [17], respectively.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A total sample of 71,036 pregnant women were included in the analyses. Among the 10 studies, six studies were conducted in USA [15,18,20,22], two studies were conducted in Australia [16,26], and one study conducted each in Brazil [11], Canada [24], Greece [27] and Ireland [17], respectively.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…However, diabetes in pregnancy (DIP) was not included in that systematic review. In fact, there has been literature reporting data on the occurrence of antepartum depression among women with and without DIP [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Furthermore, DIP could be associated with the onset of antepartum depression.…”
Section: Introductionmentioning
confidence: 99%
“…But a review of the few studies done in this population found that the diagnosis is accompanied by a range of negative emotions such as fear, anxiety, a loss of control, and a mourning of not having a normal pregnancy, which is not well addressed by midwives or other maternal health care providers . A study of pregnant women with type 1 diabetes, GDM, and no diabetes found that women with GDM had higher levels of stress and anxiety than those with type 1 diabetes . It is well known that stress is associated with adverse pregnancy outcomes such as preterm labor…”
Section: Screening For Gestational Diabetes: One‐step Versus 2‐step Amentioning
confidence: 99%
“…Additionally, a diagnosis of GDM is a stressful life event [5][6][7][8] which has an adverse impact on self-perception towards health and quality of life [6,9]; as well as increased odds of experiencing emotional distress. Previous studies reported that the prevalence of depression among women sufferers from GDM stood at 56.7%, while anxiety was 57.7%, and stress was even higher at 62.8% [10][11][12]. GDM and perinatal mental problems undeniably affect all members of the family [13].…”
Section: Introductionmentioning
confidence: 97%